Translatio imperii: John Dryden Aeneis-fordítása és az angol eposz - Komáromy, Zsolt (Studia Litteraria, 2016)
This article discusses some contexts and internal features of John Dryden’s translation of Virgil’s Aeneid in order to show why and how this work can be viewed within the tradition of English epic poetry. It takes issue with the view that Dryden would have suffered from an anxiety of Milton’s influence and that his translation would be a sign of the incapacity of producing original epic poetry after Paradise Lost. It is suggested that “translation” should be seen in a wider sense of a creative and critical relation to the past that is nonetheless upheld in the context of the epic’s function of legitimating national foundations. Through discussions of Dryden’s views on epic poetry, his relation to Milton, his interpretation of Virgil, and his cultural position and aims in the 1690s, the article seeks to show why we have good reasons to think of Dryden’s English Aeneid as a vital example of the epic genre, and that it can profitably be read within its tradition.